COLLABORATIVE GOVERNANCE ANALYSIS IN THE DEVELOPMENT OF WITNESS IN THE OLD CITY OF LARGE - Siti Chaerunisa; Suryoto Suryoto; Johar Mamuri (Department of Public Administration, University Wijaykusuma Purwokerto, 2023)
Tourism has a complex nature, therefore in managing tourism there needs to be cooperation between the government, the private sector, and the community so that tourism can develop properly so that it can provide benefits for humans. In connection with this, the Banyumas sub-district government in developing the tourism sector in the Old City of Banyumas has collaborated with the private sector and the community to hold Banyumas Peken activities. The purpose of this study was to analyze and describe collaborative governance in the development of Peken Banyumasan tourism in the Old City of Banyumas, Banyumas District, Banyumas Regency. The research method used is a qualitative descriptive method whose purpose is to describe the actual situation that occurred at the research location. The method of determining the informants used a purposive sampling technique. Methods of data collection through observation, in-depth interviews, and documentation. The data analysis method uses the interactive model Miles, Huberman, and Saldana. This study uses collaborative governance theory according to Ansell and Gash (2007: 544) which includes aspects of initial conditions, institutional design, facilitative leadership, and collaborative processes. This research found that collaborative governance in tourism development efforts can be carried out properly.